THE ROLE OF HORMONE REPLACEMENT THERAPY IN PATIENTS WITH OSTEOPOROSIS AND PERIODONTAL DISEASE - Georgeta Maria Laza; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Diana Anton; Raluca Mocanu; Liliana Pasarin; Petra Surlin (Romanian Dental Association for Education, 2020)
The number of patients undergoing hormone replacement therapy (HRT) to counterbalance hormonal changes is increasing. Patients follow HRT not only to avoid climatic symptoms but also to protect themselves from cardiovascular disease and osteoporosis. HRT is an option for women who need drug therapy to reduce the risk of osteoporosis, including women at high risk of fracture for the next 5-10 years. Oestrogen supplementation can modulate the periodontal destruction rate through mechanisms involving inhibition of matrix metalloproteinases (MMP-8 and MMP-13) and cytokines involved in bone resorption